2021
DOI: 10.1108/jfc-01-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Public sector fraud: the Malaysian perspective

Abstract: Purpose This paper aims to explore and compare the perception of public sector employees on fraud and associated fraud behaviours. Design/methodology/approach The population of this study comprised 44 managers from the Malaysian Federal government departments. The analysis was based on an open-response questionnaire using data-driven thematic analysis. This was based on the context and latent content of the respondents. The items in the questionnaire examined the perceived definition, actions and experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
(64 reference statements)
0
13
0
1
Order By: Relevance
“…Individuals with low self-esteem, by comparison, usually use money to 'cover up' for their poor self-esteem (Jiang et al, 2015) and to require reputation and many possessions to identify themselves (Mogilner & Aaker, 2009). In addition, fundamental awareness of fraud is important in distinguishing a person from being an ethical or dishonest person, which could deter the possibility of corruption (Zahari et al, 2021). Sathappan et al (2016) explored the causes of bribery among law enforcement officers in Selangor.…”
Section: Hence This Study Developed the Following Hypothesismentioning
confidence: 99%
“…Individuals with low self-esteem, by comparison, usually use money to 'cover up' for their poor self-esteem (Jiang et al, 2015) and to require reputation and many possessions to identify themselves (Mogilner & Aaker, 2009). In addition, fundamental awareness of fraud is important in distinguishing a person from being an ethical or dishonest person, which could deter the possibility of corruption (Zahari et al, 2021). Sathappan et al (2016) explored the causes of bribery among law enforcement officers in Selangor.…”
Section: Hence This Study Developed the Following Hypothesismentioning
confidence: 99%
“…Most hexagon frauds were tested in public sector organizations [6][7] [8]; only [9] examined publicly listed companies on the stock exchange. The difference is, this study examines all industrial sectors of companies listed on the Indonesia Stock Exchange (IDX) while [9] only examines the banking sector.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main categories of occupational fraud, which are assets misappropriations, corruption & financial statement fraud. Malaysian public sectors are frequently confronted with issues of fraud involving senior leadership in relation to the corruption, abuse of power by leaders and criminal breach of trust (Zahari et al, 2021). The public procurement is defined as "the acquisition of supplies, services and works by the Government (Abul Hassan et al, 2020, p.1).…”
Section: Introductionmentioning
confidence: 99%
“…The report which also had demonstrated a significant alarming increase of arrested public officials by MACC. Zahari et al (2021) found that the Malaysian public sector is one of the sectors that have issues with the occupational fraud where there are cases involving top political leaders in the country, whereby the fraudster was found guilty by the High Court of Malaysia for committing fraud including abuse of power, criminal breach of trust, and money laundering belonging to companies that the Federal Government has the interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation